Bermudagrass Under Different Fertility and Harvest Management Practices - B. C. Pedreira; D. Helwig; M. Haywood; J. K. Farney; G. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2022)
A second year of a bermudagrass fertility study was conducted at the K-State Research and Experiment Station outside of Columbus, KS, in 2021. The purpose of the study was to simulate forage producers’ practices of managing bermudagrass and determine how each practice affected forage production and quality.
Keywords: fertilizer; perennial forage; forage quality; crude protein